2020
DOI: 10.1111/odi.13267
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of burning mouth syndrome profiles based on response to a local anaesthetic lozenge

Abstract: Objective Burning mouth syndrome (BMS) is a chronic oral pain condition with unknown aetiology but assumed to involve peripheral/central neuropathological and immune‐mediated inflammatory factors. We aimed at characterizing inflammatory and neurogenic profiles and oral symptomatology of patients with BMS based on response to a local anaesthetic lozenge. Methods Patients with BMS were divided into an Effect (n = 13), No effect (n = 8) or Unspecified (n = 2) group according to their response to a local anaesthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Treldal et al [88] found that the plasma levels of IL-6, IL-8, IL-17, IL-23, and TNF-α were higher in BMS patients who were not given a local anaesthetic than in those who were, but without significant differences (p-values: 0.068-0.916). Only IL-6 was significantly elevated in the stimulated parotid saliva for the no effect group (p = 0.020).…”
Section: Functional Brain Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Treldal et al [88] found that the plasma levels of IL-6, IL-8, IL-17, IL-23, and TNF-α were higher in BMS patients who were not given a local anaesthetic than in those who were, but without significant differences (p-values: 0.068-0.916). Only IL-6 was significantly elevated in the stimulated parotid saliva for the no effect group (p = 0.020).…”
Section: Functional Brain Imagingmentioning
confidence: 99%
“…Bio-Histopathological Study 3.5.1. Cytokine Levels Among the six articles, five were case-control studies [83][84][85][86][87] and one was an RCT [88] (Table 1).…”
Section: Functional Brain Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease often occurs in postmenopausal women and is often accompanied by dry mouth. Numerous local and systemic (40,41). This study aimed to systematically examine the salivary biomarkers IL-6, IL-1β, and TNF-α in BMS.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 patients report no symptoms upon waking, with a gradual increase in pain throughout the day, reaching maximum intensity at night. This variant has been associated with systemic conditions such as nutritional deficiency and diabetes, reflecting the influence of metabolic and nutritional factors on the manifestation of BMS [5].…”
Section: Type 1: Progressive Daily Painmentioning
confidence: 99%